Uso de OKR para diseñar un modelo de negocios Canvas: el caso de una PYME Argentina - Primo, Ariel Germán (2024)
This research proposes the design of a model for the sale of components, spare parts, and bicycles through an online platform. The case illustrates the combined use of two highly popular tools: Objectives and Key Results (OKRs) and Canvas. The paper presents how a small and medium enterprise (SME) used the OKR agile methodology to map a new business model. Regarding the research methodology used, it is descriptive and uses a qualitative approach in the shape of a case study. Data were collected using direct observation. The data were collected in the location where the company being studied operates. The study concludes that it is plausible to apply the OKR methodology in a different way from usual, by developing and implementing the steps to achieve the objective and key results of a new business unit belonging to a small family business in a regional economy within Latin America. The main benefit identified is learning the priorities or key results expected by the relevant individuals in charge, which contributes to improvement the organization's performance since it helps link workers with the company's strategic objectives and take timely actions to achieve the expected progress.